Through Their Gaze: Ethics and Ecology in Ḥadīth = ḥīn tnṭq ālkāīʾnāt: ālbʿd ālbīīʾī lbʿḍ ālāʾḥādīṯ ālnbūīa ālšrīfa - Tlili, Sarra (Journal of Islamic ethics, 2025)
This article examines Ḥadīth’s strategy of presenting events from the standpoint of nonhuman beings as a means of disrupting human exceptionalism. Ample evidence shows that Ḥadīth’s moral vision encompasses the entire created order; close analysis of a set of narratives illustrates one of the ways Ḥadīth achieves this goal. By giving nonhumans a voice and centering their perspectives, Ḥadīth portrays them not as passive resources but as active stakeholders in the moral order - capable of evaluating human conduct and directly experiencing its effects, for better or worse. This shift in vantage point is powerful because it decenters the human viewpoint, awakening Ḥadīth’s audiences to the needs and vulnerabilities of other creatures and to the ways human actions impact them. In this moral universe, human worth is not inherent but contingent on piety, ethical conduct, and the capacity to coexist respectfully with other beings. By situating humans within a broader creaturely community and underscoring their interdependence, these ḥadīths advance an ethic of mutual respect, restraint, and care - an ethic with urgent relevance in an era of environmental degradation, biodiversity loss, and climate crisis.